Perbandingan Hasil Belajar Menggunakan Model Pembelajaran Problem Posing dengan Problem Solving Pelajaran Sejarah - Josua Fernando; Muhammad Basri; Suparman Arif (FKIP UNIVERSITAS LAMPUNG, 2019)
The purpose of this study was to determine the differences of the students’ learning outcomes between those who were being taught by using problem posing learning models and those with problem solving learning models in history subjects of XI social studies class at SMA Negeri 1 Terbanggi Besar, Lampung Tengah. The research method used is the experimental design method and the form of the postest only control design. The results of data analysis showed that there were differences in learning outcomes between students using problem posing learning models and problem solving learning models in historical learning.Tujuan penelitian ini adalah untuk mengetahui perbedaan hasil belajar siswa antara yang diajar menggunakan model pembelajaran problem posing dengan model pembelajaran problem solving pada Mata Pelajaran Sejarah Kelas XI IPS di SMA Negeri 1 Terbanggi Besar Lampung Tengah Tahun Ajaran 2017-2018. Metode penelitian yang digunakan adalah metode experimental design dan bentuk posstest only control design. Hasil analisis data menunjukkan ada perbedaan hasil belajar antara siswa yang menggunakan model pembelajaran problem posing dengan model pembelajaran problem solving pada pembelajaran sejarah.Kata kunci: hasil belajar, problem posing, problem solving